Dramat, dramaturgia, dramatologia – retroperspektywy - Kosiński, Dariusz (Przestrzenie Teorii, 2021)
The article is an attempt to reconsider, reinterpret and, at the same time, summarize the concepts of dramaturgy and dramatology as they were developed by the author mainly in his research realized within the framework of the Chair of Drama and then the Chair of Performance Studies at the Jagiellonian University. Despite the fact that efforts to establish a broad understanding of drama and dramaturgy that is not restricted to art but is used to analyse and interpret performative aspects of social life were not fully successful, the main goal of the article is to support this idea by claiming the need for a ‘return to dramatology’.